Pengaruh Perhatian Orang Tua Terhadap Hasil Belajar PAI Siswa Kelas VII Di SMP Negeri 7 Bukittinggi - Rahmana, Sitto (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
Education is a shared responsibility between families, communities and the government. School is only a helper for the continuation of education in the family, because the first and foremost education a child gets is from the family. The child's attitude towards school will mainly be influenced by the attitude of his parents. Parents must pay attention to their children's schooling, that is by paying attention to their experiences and appreciating all their efforts. In this study, it will examine the attention of parents to the learning outcomes of PAI class VII students of SMP 7 Bukittinggi. Based on the results of the variable analysis calculations carried out, by accepting the first hypothesis (H1) and rejecting the null hypothesis (Ho) where the calculated F value is greater than the F table value at a significant level of 5% with db reg b/a = 1 and dbres = 27-2 = 25, that is 91.58 > 4.24. This means that parental attention has a positive effect on students' Islamic education learning outcomes, with a coefficient of determination of 0.7849. These results indicate that the magnitude of the contribution of parental attention to student learning outcomes of PAI is 78.49%, while the remaining 21.51% is determined by a number of other factors such as the student's own internal factors, such as physical factors (health) and psychological factors (motivation, attention and concentration) or from other external factors, such as friends and teachers. This is in accordance with the opinion of Naglim Purwanto who said that there are three kinds of educational environment, namely the family environment, school environment and community environment.